CREATIVE DANCE LESSONS IN IMPROVING THE CREATIVITY OF CHILDREN with special needs in SLB-G-G ''DAYA ANANDA " YOGYAKARTA - Dyan Indah Purnama Sari (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2017)
Â AbstractChild with special needs is if there is something less or even more in him. There is a strong connection between the daily movement patterns and dance patterns with how the behavior of children with special needs to interact with the surrounding environment. Movement which is projected by special needs children are reflection of the level of their confidence. Through creative dance movement with special needs children need to be helped to feel confident that their existence can be equated with normal children. Daily motion used in movement therapy helps excitatory motor coordination body of the child in order to be able to realize themselves without limits. The creative dance learning model is the educator tools to track the level of a creative intelligence in solving the existing problems on himself. Creative learning in dance at least include aspects; exploration, improvisation, incubation and results. In the exploration of this movement is the child trying to find themselves, but of dancing motion is only used as a motion experience whose activities led or child-centered. Mobility of motion can be used as an orientation in enhancing creativity in children with special needs SLB-G Daya Ananda Yayasan Sayap Ibu Kalasan Yogyakarta. This qualitative study describes how the implementation process of creative dance learning model.